Changes in the Perceptions of Oral Symptoms Due to COVID-19 in Korean Adolescents - Sun-Kyoung Lee; Jeong-Min Seong (MDPI AG, 2023)
This study investigated the oral symptoms and subjective health perceptions of Korean adolescents due to COVID-19. Data from the 17th Korea Youth Risk Behavior Survey (KYRBS; 2021) were analyzed, and 54,848 Korean middle and high school students were included in the study. Frequency, cross-tabulation, and logistic regression analyses were performed using IBM SPSS (v. 22.0; IBM Corp., Armonk, NY, USA). Statistical significance was set at p < 0.05. The survey results on subjective health perception showed that 64.8% considered themselves "healthy", 26.1% rated themselves "moderate" in health, and 9.26% rated themselves "unhealthy." When asked about brushing their teeth after lunch at school, students answered "no" more frequently than "yes". Participants provided significantly different responses to questions related to receiving "sealant treatment", "having broken teeth", "experiencing tooth pain when eating", "having throbbing tooth pain", and "having pain and bleeding in gums". Regarding the relationship between oral symptoms and subjective health perceptions due to COVID-19, students perceived themselves as healthy when they had no throbbing tooth pain, risk of pain, bleeding in the gums, or symptoms of toothache when eating. Results reveal a relationship between oral symptoms and subjective health perceptions due to COVID-19. Thus, appropriate oral health management for adolescents is needed in response to the COVID-related changes.